Non-identical particle femtoscopy in models with single freeze-out - Kisiel,Adam (2007)
We present femtoscopic results from hydrodynamics-inspired thermal models with single freeze-out. Non-identical particle femtoscopy is studied and compared to results of identical particle correlations. Special emphasis is put on shifts between average space-time emission points of non-identical particles of different masses. They are found to be sensitive to both the spatial shift coming from radial flow, as well as average emission time difference coming from the resonance decays. The Therminator Monte-Carlo program was chosen for this study because it realistically models both of these effects. In order to analyze the results we present and test the methodology of non-identical particle correlations.